El yacimiento achelense de as Gándaras de Budiño: sín-tesis y perspectivas después de 50 años de desencuentros - Méndez-Quintas, Eduardo (2018)
The Acheulean site of As Gándaras de Budiño: synthesis and perspectives after 50 years of disencoutersAs Gándaras de Budiño (GB) is a key locality for the Lower Palaeolithic record of the Iberian Peninsula. Although the site has been excavated in different occasions over the last decades, several geological and archaeological aspects are still not well known. Among other issues, the age of the lithic assemblage has been debated for a long time: despite an initial correlation to the MIS 2, new evidence rather points towards a Middle Pleistocene age instead. The lithic assemblage characterized as large flake acheulean type (LFA), with many similarities with other acheulean sites in the Iberian Peninsula. This work presents an updated overview of the current state of knowledge for GB while a new multidisciplinary research project has been recently initiated